Air quality services on climate time-scales for decision making: An empirical study of China. (20th August 2021) - Wan, Kai; Shackley, Simon; Doherty, Ruth M.; Shi, Zongbo; Zhang, Peiqun; Glenk, Klaus; Bo, Xin; Chang, Luyu; Feng, Zhiqiang; Hewitt, Chris D.; Wang, Qian; Xu, Jianming; et al.
Abstract: The provision of climate services for assessing and governing environmental problems such as poor air quality requires interactions between scientists and decision-makers. Air quality information services in China mainly focus on the coming days to weeks. However, users may benefit from air quality information on climate time-scales—from months to decades; hereafter air quality climate services. We focused on key decision-makers and stakeholders that are users of air quality climate services and conducted five workshops with these identified users to ascertain their priorities for air quality climate services, and the reasoning behind these priorities. We also conducted a choice-based conjoint experiment via an online survey distributed amongst regional and local Climate Centres and Environmental Monitoring Centres to assess quantitatively the decision-makers' needs. The results from the workshops and the survey showed that the needs for air quality climate services by users in China mainly relate to seasonal forecasting of winter haze events (PM2.5 levels and/or the meteorological conditions conducive to the dispersion of the air pollution); there is also some interest in long-term projections of haze under climate change and a growing interest in ozone pollution in summer. Spatial relevance is perceived to be important to regional and city-level stakeholders who prefer information on the city-level, whilst national-wide information is important for national government agencies. A high level of reliability of forecasts was needed for uptake. The findings on the needs for air quality climate services by potential users can support researchers and policy-makers in developing the scientific capacity and providing tailored and effective air quality climate services in China. Highlights: To understand decision-maker needs on air quality climate services, qualitative and quantitative methods were conducted, and the results were compared and combined. Decision-makers and stakeholders expressed a strong interest for seasonal forecasting for winter haze. They also expressed a moderate interest for seasonal forecasting for summer ozone pollution, and a modest interest for long-term projections of haze under climate change. A high level of reliability of forecasts was needed for uptake while multiple sources of uncertainties were recognised.